Transformasi Digital UMKM di Indonesia: Analisis Data Sekunder pada Ekosistem E-commerce dan Ekonomi Digital 2024 - Khoiyum Putri Rahayu; Fadia Putri Illa; Alifvia Fasiha Lahja (Publikasi Riset Mahasiswa Manajemen, 2026)
This study aims to analyze the dynamics of digital transformation of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia using a secondary data analysis approach. Amidst the rapid growth of the digital economy, MSMEs face both challenges and significant opportunities in adopting e-commerce technology. Data used in this study are sourced from the Central Statistics Agency (BPS), the Ministry of Cooperatives and SMEs (Kemenkop UKM), the e-Conomy SEA 2024 industry report, and big data insights from social media platforms and marketplaces. The analysis results show that although the number of digitalized MSMEs continues to increase, reaching the target of 30 million by 2024, structural barriers remain in terms of digital literacy and market access. The integration of traditional marketplace platforms with social commerce (video commerce) is a dominant trend driving the Gross Merchandise Value (GMV) of Indonesian e-commerce to reach $65 billion by 2024. This study provides policy recommendations for the government and industry players to strengthen the MSME digital ecosystem through a data-driven approach.